A Recommendation System to Analyse SDCCH Using Data Munging for Communication Network (International Journal of Innovative Research in Engineering & Management, 2022)
The recommendation system in  communication network plays an important role to  recommend the end user for their choices, while analysing  the browsing patterns it forecasts user’s preferences for the  thing. To facilitate required useable contents and  information from the web data and to increase the system  performance in hilly and mountain terrain areas where  there are lots of communication network challenges, the  data munging based on collaborative filtering technique is  employed. To provide easy operations on e-commerce  sites, online shopping sites and online income sites; the  proposed recommendation system delivers better results in  term of accuracy while considering high network  congestion, channel traffic rate, SDCCH (Standalone  Dedicated Control Channel) block calls sites, cell use,  SDCCH dropping percentage, TCH (Traffic Channel)  drop, handover, total cell derivatives, total site calls and  losing sites.
Keywords: Recommendation System; Data Munging; Collaborative Filtering Algorithm; SDCCH; TCH